Pengaruh Stres dan Hubungannya Dengan Pekerjaan Dalam Perilaku Organisasi - Zulqaidah; Ella Nurmaini; Maidiana (CV Edujavare Publishing, 2023)
This study aims to describe or explain the literature review of work stress in organizational behavior. The method of this research uses qualitative research method using a literature study approach or with a lifestyle-based study through the surgical book and journals. Research steps start from the collection of articles, reduction articles, discussions and conclusions. The results showed that the work of stress work in organizational behavior, stress-type, the factors cause the stress of work, the impact of work stress on performance, the way to cope with stress. This is the one of the relationships of work stress in organizational behavior. The factors that cause stress are seen from the work environment and a person's personal environmental factors. Several factors that cause work stress include: Work that requires excessive demands.